Again, Knowledge of Common Source Fails to Promote Visual-Haptic Integration. Issue 1 (February 2014) - Misceo, Giovanni F.; Jackson, Sarju V. S.; Perdue, Jessica R.
The present study tested whether knowledge of a common source of conflicting visual-haptic stimulation promotes intersensory integration. 40 undergraduates manually felt the size of a square while viewing it through a lens that minified its visual size by half. Participants, however, could experience the haptic and the visual stimulation as emanating from either a common source or different sources. Their subsequent matches of the perceived size were biased by the felt size of the square, irrespective of whether they experienced the intersensory stimulation as coming from one or two sources. These results strengthen previous findings suggesting that the integration of sensory discordant information depends on bottom-up rather than on top-down processes.